Los factores de riesgo psicosocial y su incidencia en el estrés, contexto de pandemia Covid 19 en la Pontificia Universidad Católica del Ecuador Sede Esmeraldas - Ramírez Naranjo, Rosa Elvira (2023)
The present research was executed with teaching, administrative and workers of the Pontificia Universidad Católica del Ecuador Sede Esmeraldas (PUCESE), the objective is to examine the psychosocial risk factors and their incidence on stress. The methodology used is qualitative quantitative, non-experimental, correlational and cross-sectional. In the methodology, the CoPsoQ-istas21(V2) method was used, for the first variable and the Maslach Burnout inventory (MBI) the burnout syndrome due to work stress assistance, the instruments have reliability, validity and relevance. The results validate the central hypothesis the psychosocial risk pace of work (93.5%) with stress levels (high) by sex, men X2 = 122.8 and Cramer's coefficient V = 212.8 acceptable association and women X2 = 11.9 and with V = 66.01 acceptable association.More favorable psychosocial risks for both sexes: development possibilities 85.4%, sense of work 82.1%, vertical confidence 90.2%, recognition 87%, justice 73.2%, demands to hide emotions 52.8%. The factors that affect most unfavorably: emotional demands 51.2%, social support from colleagues 58.5%, job insecurity 59.3%, insecurity about working conditions 60.2%, role conflict 61% and work rhythm 93.5%. High stress levels, female sex: Emotional fatigue (EC) 17%, Depersonalization (PD) 10% and Personal fulfillment (PR) 31%. Medium EC 30%, DP 34% and PR 32%. Low EC level 27%, DP 30% and PR 11%. For the male sex high PD 50%. Medium EC 9% and low level EC 41% and PR 50%. The conclusions indicate a higher incidence of psychosocial risk and stress for females versus males. The proposal is designed with strategies from a comprehensive vision from Human Talent, work teams and workers in order to ensure an effective impact in the short and long term that conforms to the protocol of psychosocial risks.